2017
DOI: 10.1021/acs.jpcc.7b03728
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights on the CH4/CO2 Separation in Nanoporous Graphene and Graphene Oxide Separation Platforms: Adsorbents versus Membranes

Abstract: Molecular dynamics simulations were performed to gain fundamental molecular insights on the concentration-dependent adsorption and gas transport properties of the components in a CH4/CO2 gaseous mixture in single- and double-layered nanoporous graphene (NPG) and graphene oxide (NPGO) separation platforms. While these platforms are promising for a variety of separation applications, much about the relevant gas separation mechanisms in these systems is still unexplored. Based on the gas adsorption results in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 68 publications
4
38
0
Order By: Relevance
“…For application as selective membranes, the use of thicker laminates is usually accompanied by a compromised gas permeability, including CO 2 . Researchers have sought several strategies to overcome this drawback, which include using porous (holey) graphene nanosheets to facilitate a more direct CO 2 transport (Figure 3b), chemical functionalization to increase the affinity for CO 2 (Figure 3c) and intercalation by spacers to increase the interlayer spacing between the GO nanosheets (Figure 3d) [5,40,41]. To this end, the most commonly used spacers include ionic liquids, various ions (such as metal and borate ions), as well as a multitude of CO 2 -philic amine-based crosslinkers [5,33,[42][43][44].…”
Section: Few-to Multi-layer Graphene-based Stacked Laminatesmentioning
confidence: 99%
“…For application as selective membranes, the use of thicker laminates is usually accompanied by a compromised gas permeability, including CO 2 . Researchers have sought several strategies to overcome this drawback, which include using porous (holey) graphene nanosheets to facilitate a more direct CO 2 transport (Figure 3b), chemical functionalization to increase the affinity for CO 2 (Figure 3c) and intercalation by spacers to increase the interlayer spacing between the GO nanosheets (Figure 3d) [5,40,41]. To this end, the most commonly used spacers include ionic liquids, various ions (such as metal and borate ions), as well as a multitude of CO 2 -philic amine-based crosslinkers [5,33,[42][43][44].…”
Section: Few-to Multi-layer Graphene-based Stacked Laminatesmentioning
confidence: 99%
“…A similar diameter was also proven to filter salt ions from water during desalination [26]. In comparison, A. Khakpay et al [31] showed that CH 4 permeance is even larger than the one of CO 2 through a larger elliptic pore (10-12 Å). Such a behavior indicates that, beyond a critical diameter, steric hindrance no longer contributes to selectivity and that for the natural gas purification to take place one must rely on other factors such as pore shape and functionalization.…”
Section: Resultsmentioning
confidence: 95%
“…Please do not adjust margins Moreover, our unique approach has the advantage of allowing for complex analysis of multi-component gases which are not easily attainable through studies involving potential of mean force (PMF) analysis. Specifically, when comparing our membrane system to the membrane systems studied by Khakpay et al, we make two important distinctions between a MIL-160 membrane and nanoporous graphene (NPG) and nanoporous graphene oxide (NPGO) sheets that ultimately confound the simplicity with which a PMF analysis could be implemented for the MIL-160 membrane 82 . First, the inherent cage-like geometry of the MIL-160 membrane poses geometrical limitations on the umbrella sampling routine that would be invoked to determine the binding affinity of a particular gas molecule to MIL-160.…”
Section: Competitive Adsorption Processes Within the Mil-160 Membranementioning
confidence: 99%